Places of possibility : property, nature and community land ownership - Mackenzie, Fiona (A. Fiona D.) (Chichester, West Sussex, UK ; Malden, MA : Wiley-Blackwell, 2012)
Through original research conducted in the Outer Hebrides, Scotland, Places of Possibility shows how community land ownership can open up the political, social, environmental, and economic terrain to more socially just and sustainable possibilities than private ownership. Reveals how community land ownership is more just and sustainable than private ownership -- Features original theoretical insights into ideas of property and nature that disrupt the process of neoliberalisation -- Based on original research conducted by the author in the Outer Hebrides, Scotland.
Placing possibility -- Working property -- Working nature -- Working the wind -- Working places -- Conclusion -- working possibilities.
Includes bibliographical references and index.
Description based on print version record and CIP data provided by publisher.
Keywords: Land reform -- Scotland; Land tenure -- Scotland; Commons -- Scotland; Right of property -- Scotland; BUSINESS & ECONOMICS / Real Estate / General; Right of property - Scotland; Commons; Land reform; Land tenure; Right of property; Scotland; Electronic books; Electronic books